Clinical Pharmacist’s Role in Optimizing Therapy through Drug-Related Problems Identification - Liana Debora; Eni Susanti; Suharjono Suharjono (Universitas Padjadjaran, 2021)
Clinical pharmacists play an important role in a clinical setting as part of a team. Drug-related problem (DRP) is the main part pharmacist should focus on to achieve the optimal therapy for patients. Therefore, this study aimed to investigate the role of clinical pharmacy in a private hospital of West Java, Indonesia, and describe the prevalence of DRPs and several factors associated with the risk of DRPs. The clinical pharmacist's monthly report was obtained from June to August 2020. Furthermore, problems, causes, and types of DRP were identified using PCNE Classification V9.1. Drug classes and other factors related to DRP were also investigated. This was a descriptive study with a retrospective approach to medical records, where 240 DRPs were identified in 157 patients. Approximately 4.45% experienced DRP, especially in ICU at 45.83% and Stroke Unit or SU-IC at 25.42%. The most common DRPs were incomplete drug treatment, drug interaction, and dose adjustment. Antimicrobial, cardiovascular agents, and PPI were the most commonly involved. In the linear regression analysis, length of stay and number of therapy significantly affect DRP. In this study, pharmacists intervented each DRP, with 57% accepted as fully and partially implemented by the physicians. A total of 22% of interventions ended with unknown status due to limited follow-up time. Meanwhile, reviews on medication by clinical pharmacists lead to improvement in drug treatment. The implementation of clinical pharmacy services shows many DRPs to be prevented and increases therapy optimization.Keywords: Clinical pharmacist, drug-related problems, drugs, hospital, intervention Peran Farmasis Klinis dalam Optimalisasi Pengobatan melalui Identifikasi Permasalahan Obat AbstrakFarmasis klinik memiliki peran penting dalam tim di RS terutama dalam mencapai terapi optimal bagi pasien melalui penanganan drug related problems (DRP). Tujuan penelitian ini adalah untuk mengetahui peran farmasis klinik di salah satu RS swasta di Jawa Barat dan faktor risiko terjadinya DRP. Data dari laporan farmasi klinik diambil pada bulan Juni–Agustus 2020. Identifikasi permasalahan, penyebab, jenis DRP dilakukan berdasarkan PCNE Classification V9.1. Golongan obat dan faktor lain yang menyebabkan DRP juga dikaji. Studi ini berupa penelitian deskripsi dengan pendekatan retrospektif berdasarkan rekam medik pasien. Farmasis mengidentifikasi 240 DRP pada 157 pasien rawat inap. Sekitar 4,45% pasien di RS berpotensi mengalami DRP, terutama yang dirawat di ruang perawatan intensif (45,83%) dan unit strok (25,42%). DRP yang paling sering terjadi adalah terapi obat kurang tepat, interaksi obat, dan perlunya penyesuaian dosis. Antimikroba, obat kardiovaskular, dan PPI merupakan obat yang paling sering menyebabkan DRP. Pada analisis statistik menggunakan regresi linier, lama perawatan dan jumlah jenis obat signifikan menyebabkan DRP. Farmasis menyampaikan usulan kepada dokter (>70% kasus). Sebanyak 22% usul berakhir dengan status yang tidak diketahui karena kurangnya waktu untuk follow up usul kepada dokter. Tingkat penerimaan usul yaitu 57%, baik yang diterima sepenuhnya maupun diterima sebagian. Pengkajian pengobatan pasien mendorong beberapa perbaikan terapi obat. Penerapan layanan farmasi klinis dapat mendeteksi dan mencegah DRP sehingga mengoptimalkan pengobatan pasien. Kata kunci: Drug-related problems, farmasis klinik, intervensi, obat, rumah sakit